Some Sex Hormone Profiles Are Consistent Over Time in Normal Menstruating Females: Implications for Sports Injury Epidemiology - Shultz, Sandra J. (2009)
PURPOSE: It is unclear whether sex hormone profiles obtained in two consecutive months are consistent within females. We prospectively examined month to month consistency in daily, nadir, peak and mean hormone concentrations during the early follicular and luteal phases in recreationally active, young eumenorrheic females. METHODS: 60 healthy, non-smoking females who reported normal and consistent menstrual cycles lasting 26–32 days for the past 6 months were followed prospectively to obtain serum samples for the first 6 days of menses, and for 8 days following a positive ovulation test over two consecutive months. Month to month consistency of daily concentrations of estradiol (pg/mL), progesterone (ng/mL), testosterone (ng/dL), SHBG (nmol/L) and FAI were determined using linear mixed models. Month to month consistency in nadir, peak and mean concentrations were then assessed using intraclass correlation coefficients (ICC) and standard error of the measurement (SEM) to more precisely examine intra-individual consistency. RESULTS: Linear mixed models revealed stable hormone concentrations across cycles and cycles by day. Reliability estimates for nadir, peak, mean menses and mean postovulatory concentrations range from 0.56 – 0.86 for estradiol, 0.44 – 0.91 for progesterone, 0.60 – 0.86 for testosterone, 0.88 – 0.97 for SHBG, and 0.78 – 0.91 for FAI. CONCLUSIONS: Hormone profiles were reproducible over two consecutive months. In order to reduce month to month intra-individual variations and improve measurement consistency, it is recommended that multiple samples be taken over consecutive days as opposed to a single sample.